(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the linguistic features of terms as a special layer of vocabulary in a language. It discusses the origin, structure, semantic characteristics, and functional peculiarities of terms used in various scientific fields. Particular attention is given to the processes of term formation, including borrowing, word formation, abbreviation, and semantic extension. The study emphasizes the importance of linguistic accuracy and standardization in terminology to ensure clarity and efficiency in scientific communication. Furthermore, the paper highlights the role of globalization and technological advancement in the enrichment and transformation of modern terminology systems. Comparative examples from Uzbek and international linguistic practices are also provided to illustrate the dynamics of term development.